(untitled) (Research, Society and Development, 2022)
It is known that the widespread use of drugs has consequences and impacts, as it can result in adverse effects and in the quality of life of the patient. Faced with this problem, the existence of unsuitable drug detection criteria for older people is clarified, such as the Beers criterion. In view of the above, the objective of this study is to evaluate, through the analysis of medical records, which drugs and how many potentially inappropriate drugs for the elderly are used in a health center located in the city of Teresina, state of Piauí. In methodological terms, this study was developed through an exploratory field investigation, following a quantitative approach of data analysis. The data were obtained in the scope of the Centro Integrado de Saúde (CIS), Teresina/PI, after the consent of the institution that holds the records. The study sample is composed of 74 (seventy and four) clinical histories of patients over 60 years of age treated at the aforementioned study site in 2019. Based on the data obtained in this investigation, it is evident that most of them Participants are female, have more than 70 years of age and present as prevalent morbidities Systemic Arterial Hypertension (SAH) and Osteoporosis. It was evidenced that the main needs of the analyzed patients who sought medical attention were memory loss/mental confusion, muscle pain and symptoms of depression and sadness. A higher prevalence of medical prescription was also noted in the mentioned place of study using the drugs Escitalopram, Quetiapine, Amlodipine, Hydrochlorothiazide, Mirtazapine and Memantine. Finally, it is important that medical professionals know the Beers criteria, highlighting the importance of knowledge about the consequences of incorrect use of medication in elderly people, deserving greater attention among those elderly who use polypharmacy.